2016
DOI: 10.1007/s00436-016-5287-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy against nematode infections and safety of afoxolaner plus milbemycin oxime chewable tablets in domestic dogs under field conditions in Europe

Abstract: Afoxolaner (AFX) plus milbemycin oxime (MO) combination chewable tablets (NexGard Spectra®, Merial) were evaluated for safety and efficacy against naturally acquired nematode infections in domestic dogs in a multi-centre, positive control, blinded field study using a randomized block design based on the order of presentation for allocation. In total, 408 dogs confirmed positive for naturally acquired infections of intestinal nematodes by pre-treatment faecal examination were studied in ten countries in Europe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
6
11
1
Order By: Relevance
“…The efficacy observed in the present field studies is comparable to the results from a recently reported European field study of similar design and methodology [10] in which geometric mean roundworm and hookworm fecal egg counts were reduced by ≥ 97.2% following a single oral dose of afoxolaner + milbemycin oxime, and by ≥ 94.3% following a single oral dose of milbemycin oxime + praziquantel (Milbemax ® ; Elanco, Greenfield, IN, USA). It was however unexpected that the combination of ivermectin + pyrantel in the present USA study only provided 74.7% efficacy against A. caninum.…”
Section: Discussionsupporting
confidence: 87%
“…The efficacy observed in the present field studies is comparable to the results from a recently reported European field study of similar design and methodology [10] in which geometric mean roundworm and hookworm fecal egg counts were reduced by ≥ 97.2% following a single oral dose of afoxolaner + milbemycin oxime, and by ≥ 94.3% following a single oral dose of milbemycin oxime + praziquantel (Milbemax ® ; Elanco, Greenfield, IN, USA). It was however unexpected that the combination of ivermectin + pyrantel in the present USA study only provided 74.7% efficacy against A. caninum.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to providing monthly flea and tick control and a deworming effect against roundworms, hookworms, whipworms, heartworm larvae and lungworm [12, 16, 17, 22], the regular monthly use of NexGard Spectra ® should indirectly help to prevent the infection of dogs by D. caninum .…”
Section: Discussionmentioning
confidence: 99%
“…NexGard Spectra ® is an oral chewable formulation containing afoxolaner, an insecticidal-acaricidal compound of the isoxazoline family, and milbemycin oxime, a nematodicidal compound [17]. It is intended to protect dogs against flea and tick infestation, and to deworm against gastro-intestinal nematodes as well as some other nematode infections ( Dirofilaria immitis , Angiostrongylus vasorum ) [9, 12, 16, 22]. Since milbemycin oxime is only nematodicidal, no efficacy is claimed against tapeworms.…”
Section: Introductionmentioning
confidence: 99%
“…In combination, the minimum therapeutic dose of afoxolaner for monthly efficacy against fleas and ticks is 2.5 mg/kg, and the minimum therapeutic dose of milbemycin oxime against adult intestinal nematode infections, and to prevent heartworm disease by interrupting the life cycle of Dirofilaria immitis, is 0.5 mg/kg (Hamel et al, 2015;Knaus et al, 2015;Kondo et al, 2015;Rehbein et al, 2015a andRehbein et al, 2015b;Tielemans et al, 2015). The calculation of the maximum exposure dose is dependent on the weight ranges developed for the commercial presentations.…”
Section: Discussionmentioning
confidence: 99%